Buckling of Prestressed Steel Girders - Bradford, Mark A. (Engineering Journal, 1991)
Prestressing of steel girders, in order to gain economy of material, is starting to become popular in the United States. An inherent danger in the stressing operation is loss of stability of the girder between the points of attachment of the tendon. The paper presents design charts for the elastic buckling load induced by stressing an eccentric tendon, and uses this to obtain a design buckling strength in accordance with the LRFD Specification.